Design and construction of an autoclave (2007)
One of the major problems confronting healthcare professionals is the control of pathogenic organisms. This is because microorganisms are present in our environment and may contaminate healthcare instruments from time to time. An autoclave was designed and constructed to sterilize materials/items used in such healthcare institutions. The autoclave has a liquid capacity of 2 litres and is heated electrically with a 2kw healing-element. The test showed a decrease in the growth of microorganisms at high temperature with a high exposure time.